2018
DOI: 10.1002/er.4179
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the heat evolution of cement slurry system using microencapsulated phase change materials

Abstract: Summary Based on the low hydration heat demand of cement slurry system used in deep water cementing, novel materials, namely, microencapsulated phase change materials (MPCMs), were synthesized and used to control the heat evolution of cement slurry by physical means. Here, the temperature profiles and hydration heat of cement slurry system were tested by using the developed semiadiabatic test apparatus. Firstly, the MPCM containing low melting paraffin wax with urea formaldehyde resin shell was synthesized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…As shown in Figure A, it was found that there is no chemical reaction between GO and UF, which belong to physical blending. Besides, as shown in Figure B, the results demonstrated that the paraffin wax was successfully encapsulated by UF or UF@GO, then, it was also found that the chemical structure of Micro‐P1 was not changed by GO, because the infrared spectra are basically the same . Therefore, GO distributed uniformly in the wall structure of Micro‐P1 only by inter‐molecular force or hydrogen bond …”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…As shown in Figure A, it was found that there is no chemical reaction between GO and UF, which belong to physical blending. Besides, as shown in Figure B, the results demonstrated that the paraffin wax was successfully encapsulated by UF or UF@GO, then, it was also found that the chemical structure of Micro‐P1 was not changed by GO, because the infrared spectra are basically the same . Therefore, GO distributed uniformly in the wall structure of Micro‐P1 only by inter‐molecular force or hydrogen bond …”
Section: Resultsmentioning
confidence: 85%
“…The thermal control mechanism of Micro‐P1 on heat evolution was investigated by phase change properties, infrared spectrum, X‐ray diffraction, thermal stability and scanning electron microscope analysis. The composition of cement slurry as presented in Table , at first, the phase change properties of mixtures (cement and Micro‐P1) was tested, and then the cement slurry was cured at 20°C for 24 hours, the IR, XRD, SEM, TG and DSC distribution curves of cement hydration products were measured and obtained …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations